Composite nanofiltration membrane with tannic acid structure as well as preparation method and application of composite nanofiltration membrane

The crosslinked tanninic acid structure composite nanofiltration membrane was prepared by steam reverse mass transfer method, which solved the problem of difficult fixation of small molecule tanninic acid in traditional coating crosslinking technology, and achieved efficient dye removal and anti-organic pollution performance , improves the flux and chlorine resistance of the nanofiltration membrane.

CN119186262APending Publication Date: 2024-12-27TIANJIN MOTIMO MEMBRANE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411242888.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In traditional solution coating crosslinking technology, small molecule tannin is difficult to act as a coating monomer independently, resulting in poor dye/salt separation performance of composite nanofiltration membranes, low flux, poor anti-organic pollution performance, and large molecules. The introduction will damage pore size regularity and increase the mass transfer resistance of water molecules.

Method used

The steam reverse mass transfer method is used to contact the aqueous tanninic acid solution with the hydrophobic base membrane, and the crosslinking tanninic acid structure composite nanofiltration membrane is prepared through the diffusion reaction of the crosslinking agent solution, which avoids the introduction of macromolecules and improves the membrane. The degree of tannin fixation on the surface.

Benefits of technology

It achieves high purity water flux and high dye removal rate, improves chlorine resistance and organic pollution resistance, and makes up for the shortcomings of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186262A_ABST
    Figure CN119186262A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of separation, and particularly relates to a composite nanofiltration membrane with a tannic acid structure as well as a preparation method and application of the composite nanofiltration membrane. The preparation method comprises the following steps: enabling a tannic acid aqueous solution to be in contact with one side of a dry hydrophobic base membrane, enabling a cross-linking agent solution to be in contact with the other side of the base membrane, and enabling cross-linking agent molecules to volatilize and diffuse through membrane pore channels in a steam reverse mass transfer manner to be in contact reaction with the tannic acid in a water phase, so as to prepare the hollow fiber composite nanofiltration membrane. Compared with the prior art, under the condition that macromolecules are not added, the cross-linked tannic acid composite nanofiltration membrane is successfully prepared through a coating cross-linking method, and the composite nanofiltration membrane shows high pure water flux and the dye removal rate close to 100%. And the cross-linked tannic acid composite nanofiltration membrane prepared by the preparation method disclosed by the invention shows relatively good chlorine resistance and organic pollution resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation, and in particular relates to a composite nanofiltration membrane with a tannic acid structure and a preparation method and application thereof. Background Art

[0002] Tannic acid, as an easily available, low-cost natural plant polyphenol, is often used in the interfacial polymerization process to prepare polyamide composite nanofiltration membranes. Its unique phenolic hydroxyl structure gives it rich negative charge characteristics and is also often used for anti-fouling modification of nanofiltration membranes. Therefore, tannic acid shows versatility in the preparation of composite membranes.

[0003] However, for traditional solution coating cross-linking technology, small molecule tannic acid is difficult to use independently as a coating monomer because of its limited reactive sites, inherent high water solubility and lack of direct adhesion, making it difficult to construct a stable and effective separation layer on the membrane surface using only small molecule tannic acid.

[0004] Therefore, researchers often combine tannic acid with hydrophilic polymers such as polyethyleneimine, polyvinyl alcohol or dopamine, and deposit them on the membrane surface through various mechanisms such as hydrogen bonding and chemical bond cross-linking to enhance the stability and density of the structure. Specifically, the following steps are included: before coating, glycerol inside the ultrafiltration membrane assembly is first removed by elution. Subsequently, a mixed solution containing hydrophilic macromolecules (including polyvinyl alcohol, polyethyleneimine, polydopamine) and small molecule tannic acid is prepared, and the aqueous phase solution is circulated into the inner surface of the hollow fiber ultrafiltration membrane, and then, a cross-linking agent solution is circulated into the inner surface of the membrane fiber, and reacted for a certain time under certain temperature conditions to prepare a hollow fiber composite nanofiltration membrane containing a cross-linked tannic acid structure. However, the co-introduction of macromolecules will destroy the regularity of the pore size of the prepared nanofiltration membrane, resulting in poor dye / salt separation performance of the prepared composite nanofiltration membrane. Moreover, the introduction of macromolecules will lead to a further increase in the thickness of the separation layer, which is likely to produce a larger water molecule mass transfer resistance, resulting in a lower flux of the prepared nanofiltration membrane. In addition, the added macromolecules are usually polyamines, which will have an adverse effect on the anti-organic pollution performance of the tannic acid structure composite nanofiltration membrane. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a composite nanofiltration membrane with a tannic acid structure and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a composite nanofiltration membrane with a tannic acid structure comprises the following steps: contacting a tannic acid aqueous solution with one side of a base membrane, and then contacting a crosslinking agent solution with the other side of the base membrane, diffusing the crosslinking agent molecules through the membrane pore channel by steam reverse mass transfer, and contacting and reacting with the tannic acid in the aqueous phase, thereby preparing the tannic acid structure composite nanofiltration membrane.

[0008] The mass concentration of the tannic acid aqueous solution is 2.0-4.0%, preferably 3.0%.

[0009] The cross-linking agent molecule is one of glutaraldehyde, ethylenediamine or diethylenetriamine.

[0010] The concentration of the cross-linking agent solution is 0.2-1%, preferably 0.5-1%, and the solvent is water.

[0011] The base membrane is a hydrophobic base membrane; preferably, the base membrane is one of polyvinylidene fluoride PVDF, polyvinyl chloride PVC, and polytetrafluoroethylene PTFE.

[0012] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically comprises the following steps: introducing tannic acid aqueous solution into the tube side of a dry hydrophobic membrane component; then, introducing and filling the shell side of the membrane component with a crosslinker solution for reaction; finally, obtaining a composite nanofiltration membrane with crosslinked tannic acid.

[0013] The reaction temperature is room temperature, and the reaction time is 30-80 min, preferably 50 min.

[0014] The present invention also comprises a composite nanofiltration membrane with a tannic acid structure obtained by the preparation method.

[0015] The present invention also includes an application of the composite nanofiltration membrane with tannic acid structure, which is applied to the removal of dyes and the separation of salts. Preferably, the dye is an anionic dye; preferably, the anionic dye is one of Congo red, reaction red 120, or orange yellow or a mixture thereof; and the salt is NaCl or Na2SO4.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] Compared with the prior art, the present invention successfully prepared a composite nanofiltration membrane with a cross-linked tannic acid structure by a coating cross-linking method without adding macromolecules, and the composite nanofiltration membrane has a higher pure water flux and a higher dye removal rate. The cross-linked tannic acid structure composite nanofiltration membrane prepared by the present invention exhibits better chlorine resistance. The cross-linked tannic acid structure composite nanofiltration membrane prepared by the present invention exhibits better resistance to organic pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1SEM surface morphology images of cross-linked tannic acid composite nanofiltration membranes prepared in (a) Comparative Example 1 and (b) Example 3.

[0019] Figure 2 The dye separation performance of the cross-linked tannic acid composite nanofiltration membrane prepared for Example 3, Comparative Example 1 and Comparative Example 2.

[0020] Figure 3 The chlorine resistance test results (pH 7; 2000 mg / L sodium hypochlorite) of the cross-linked tannic acid composite nanofiltration membrane prepared in Example 3.

[0021] Figure 4 These are the test results of the anti-organic pollution performance of the cross-linked tannic acid composite nanofiltration membrane prepared in Example 3. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0023] Example 1

[0024] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a 2.0wt% tannic acid aqueous solution is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 0.5wt% glutaraldehyde aqueous solution is introduced into the shell side of the membrane component and filled, and the reaction is allowed to stand at room temperature for 30 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0025] Example 2

[0026] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a 2.5wt% tannic acid aqueous solution is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 0.5wt% glutaraldehyde aqueous solution is introduced into the shell side of the membrane component and filled, and the reaction is allowed to stand at room temperature for 30 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0027] Example 3

[0028] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a 3.0wt% tannic acid aqueous solution is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 0.5wt% glutaraldehyde aqueous solution is introduced into the shell side of the membrane component and filled, and the reaction is allowed to stand at room temperature for 30 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0029] Example 4

[0030] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a 3.5wt% tannic acid aqueous solution is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 0.5wt% glutaraldehyde aqueous solution is introduced into the shell side of the membrane component and filled, and the reaction is allowed to stand at room temperature for 30 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0031] Example 5

[0032] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a tannic acid aqueous solution with a concentration of 4.0wt% is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 0.5wt% glutaraldehyde aqueous solution is introduced into and filled into the shell side of the membrane component, and the reaction is allowed to stand at room temperature for 30 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0033] Example 6

[0034] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a 3.0wt% tannic acid aqueous solution is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 0.6wt% ethylenediamine aqueous solution is introduced into the shell side of the membrane component and filled, and the reaction is allowed to stand at room temperature for 30 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0035] Example 7

[0036] The preparation method of the composite nanofiltration membrane with tannic acid structure specifically includes the following steps: first, using the force generated by the height difference of the liquid level, a 3.0wt% tannic acid aqueous solution is introduced into the tube side of the dry hydrophobic PVC membrane component; then, a 1.0wt% diethylenetriamine aqueous solution is introduced into the shell side of the membrane component and filled with it, and the reaction is allowed to stand at room temperature for 50 minutes; finally, a cross-linked tannic acid composite nanofiltration membrane is obtained. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0037] Comparative Example 1

[0038] The preparation method of the composite nanofiltration membrane specifically comprises the following steps: first, removing the glycerol inside the ultrafiltration membrane assembly by elution. Subsequently, using a peristaltic pump to circulate a 3.0wt% tannic acid aqueous solution through the tube of the PVC ultrafiltration membrane assembly; then, emptying the coating solution inside the membrane filaments, passing a 0.5wt% glutaraldehyde crosslinking agent aqueous solution, and reacting for a certain time under certain temperature conditions to prepare a composite nanofiltration membrane containing a cross-linked tannic acid structure.

[0039] Comparative Example 2

[0040] The preparation method of the composite nanofiltration membrane specifically comprises the following steps: first, removing the glycerol inside the ultrafiltration membrane assembly by elution. Subsequently, using a peristaltic pump to circulate a mixed aqueous solution containing 2.0wt% polyvinyl alcohol and 1.0wt% tannic acid in the tube of the PVC ultrafiltration membrane assembly; then, emptying the coating solution inside the membrane filaments, passing a 0.5wt% glutaraldehyde crosslinking agent aqueous solution, and reacting for a certain time under certain temperature conditions to prepare a composite nanofiltration membrane containing a crosslinked tannic acid structure.

[0041] Table 1 Performance test results of the composite nanofiltration membrane with cross-linked tannic acid structure prepared by the present invention

[0042]

[0043]

[0044] Note: Comparative Examples 1 and 2 used conventional solution coating cross-linking reactions.

[0045] Result analysis:

[0046] The nanofiltration membrane assembly prepared in the embodiment and the comparative example was fixed on a cross-flow filtration test device, and pure water passed through the membrane assembly under the internal pressure mode. The pressure of the cross-flow filtration test device was set at 0.30 MPa for pre-compression for 1 hour. After the membrane was completely compacted, it was tested at 0.20 MPa, and the water obtained within 10 minutes was collected, and the pure water flux was tested by weighing method; then the pure water was replaced with 0.2 g / L Congo red solution as the feed liquid for further testing, and the Congo red solution passed through the membrane assembly under the internal pressure mode. The operating pressure of the cross-flow filtration test device was 0.20 MPa, and the dye concentration in the produced water was tested using an ultraviolet spectrophotometer every 10 minutes until it was stable, and the dye retention result of the tannic acid structure composite nanofiltration membrane was calculated.

[0047] Results analysis of Examples 1-5: As the concentration of tannic acid increases, more tannic acid molecules are cross-linked and fixed on the surface of the base membrane by glutaraldehyde molecules during the reverse mass transfer reaction, so that the Congo red rejection rate of the prepared cross-linked tannic acid composite nanofiltration membrane shows a gradually increasing trend. At the same time, the increase in tannic acid concentration increases the thickness of the separation layer formed by the cross-linking reaction, and the pure water flux of the corresponding prepared nanofiltration membrane gradually decreases.

[0048] Example 3, comparative analysis of comparative example 1 and comparative example 2: Figure 1 As shown in the left figure (Comparative Example 1), after the conventional coating cross-linking reaction, broken cross-linked tannic acid separation layer fragments can be observed on the surface of the base membrane, and there are obvious defect holes on the membrane surface. In contrast, after the reverse mass transfer reaction, Figure 1 No obvious defect holes were observed on the surface of the cross-linked tannic acid composite membrane in the middle right figure (Example 3). Next, the integrity of the prepared composite nanofiltration membrane was further verified by dye retention performance test. Figure 2 As shown, the Congo red dye rejection rate of the cross-linked tannic acid composite membrane prepared in Comparative Example 1 is only 77.1%, while the Congo red rejection rate of the cross-linked tannic acid composite nanofiltration membrane prepared by the reverse mass transfer reaction is 99.5%, which is much better than the cross-linked tannic acid composite membrane prepared by the conventional coating cross-linking method using only tannic acid in Comparative Example 1. This result also proves the successful preparation of defect-free cross-linked tannic acid composite membranes under the reverse mass transfer reaction method, making up for the limitation that the conventional coating cross-linking method is only applicable to the preparation of composite nanofiltration membranes using hydrophilic macromolecules. Moreover, compared with Comparative Example 2, after adding polyvinyl alcohol to the aqueous tannic acid solution, the prepared cross-linked tannic acid-polyvinyl alcohol composite nanofiltration membrane has a high Congo red dye rejection rate of 99.0%. However, due to the presence of macromolecular polyvinyl alcohol, the thickness of the separation layer formed is greatly increased, resulting in the flux of the prepared composite nanofiltration membrane being 45.0 L·m -2 ·h -1 bar -1 , which is much smaller than 88.5 L·m-2 ·h -1 bar -1 Pure water flux.

[0049] Results analysis of Example 3, Example 6 and Example 7: Not only the small molecule cross-linking agent glutaraldehyde, but also the use of ethylenediamine or diethylenetriamine cross-linking agents can prepare defect-free cross-linked tannic acid composite nanofiltration membranes, and the Congo red rejection rate of the prepared nanofiltration membranes is greater than 98%. At the same time, under the action of small molecule monomers and reverse mass transfer reaction mechanism, the prepared cross-linked tannic acid composite nanofiltration membranes show ultra-high pure water flux results, all greater than 88.0 L·m -2 ·h -1 bar -1 .

[0050] like Figure 3 As shown, the tannic acid structure composite nanofiltration membrane prepared in Example 3 of the present invention exhibits good chlorine resistance. After being immersed in a 2000 mg / L sodium hypochlorite solution for 24 hours, the retention rate of the nanofiltration membrane for polyethylene glycol 10000 only decreased by 6.3%, and the membrane flux only increased by 14%, indicating that after 24 hours of sodium hypochlorite treatment, the tannic acid structure nanofiltration membrane still exhibits good structural stability, and the membrane pores do not change significantly, which is far superior to conventional polyamide nanofiltration membranes on the market.

[0051] 100 mg / L of natural organic matter humic acid or bovine serum albumin was selected as a typical pollutant for dynamic filtration pollution experiment. Before the test, the membrane was first moistened and cleaned with ethanol, and then the ethanol in the membrane pores was replaced with deionized water. Next, deionized (DI) water was used as the feed solution to pre-press the membrane sample at 0.30 MPa for 60 minutes. Then, the membrane was tested for pure water flux at 0.20 MPa; after 60 minutes, the deionized water was replaced with humic acid or bovine serum albumin solution, and the test run was continued. After completing one cycle, the membrane after filtering the pollutants was physically backwashed with deionized water for 60 minutes. Subsequently, the membrane flux after washing was measured again under the same conditions. Figure 4 As shown, after two cycles, the total flux attenuation rates of bovine serum albumin and humic acid were 47% and 17%, respectively. In addition, after two water washes, the cross-linked tannic acid composite nanofiltration membrane showed a relatively high flux recovery rate of 81.0% and 93.0%, respectively. Since the surface of the tannic acid structure composite nanofiltration membrane prepared by the present invention has a strong negative charge characteristic, there is no interference of macromolecular polyamine on the surface charge of the membrane, so that the tannic acid structure composite nanofiltration membrane prepared by the present invention shows good anti-organic pollution performance.

[0052] In summary, compared with the prior art, the present invention successfully prepared a composite nanofiltration membrane with a cross-linked tannic acid structure by a coating cross-linking method without adding macromolecules, and the composite nanofiltration membrane has a higher flux and a higher dye removal rate. Compared with the traditional polyamide nanofiltration membrane, the cross-linked tannic acid structure composite nanofiltration membrane prepared by the present invention exhibits better chlorine resistance. The adverse effects of macromolecules are removed, and more tannic acid is fixed on the membrane surface, so that the cross-linked tannic acid structure composite nanofiltration membrane prepared by the present invention exhibits better resistance to organic pollution.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite nanofiltration membrane with a tannic acid structure, characterized in that: The method comprises the following steps: contacting a tannic acid aqueous solution with one side of a base membrane, and then contacting a crosslinking agent solution with the other side of the base membrane; by means of steam reverse mass transfer, crosslinking agent molecules diffuse through membrane pore channels and contact and react with tannic acid in the aqueous phase, thereby preparing a tannic acid structure composite nanofiltration membrane.

2. The method for preparing the composite nanofiltration membrane with tannic acid structure according to claim 1, characterized in that: The mass concentration of the tannic acid aqueous solution is 2.0-4.0wt%.

3. The method for preparing the composite nanofiltration membrane with tannic acid structure according to claim 1, characterized in that: The cross-linking agent molecule is one of glutaraldehyde, ethylenediamine or diethylenetriamine.

4. The method for preparing the composite nanofiltration membrane with tannic acid structure according to claim 1, characterized in that: The concentration of the cross-linking agent solution is 0.2-1.0 wt %, preferably 0.5-1.0 wt %, and the solvent is water.

5. The method for preparing the composite nanofiltration membrane with tannic acid structure according to claim 1, characterized in that: The base membrane is a hydrophobic base membrane; preferably, the base membrane is one of polyvinylidene fluoride PVDF, polyvinyl chloride PVC, and polytetrafluoroethylene PTFE.

6. The method for preparing the composite nanofiltration membrane with tannic acid structure according to claim 1, characterized in that: The method specifically comprises the following steps: introducing a tannic acid aqueous solution into the tube side of a dry hydrophobic membrane component; then introducing and filling the shell side of the membrane component with a cross-linking agent solution to perform a reverse mass transfer reaction; and finally obtaining a composite nanofiltration membrane with a cross-linked tannic acid structure.

7. The method for preparing the composite nanofiltration membrane with tannic acid structure according to claim 6, characterized in that: The reaction temperature is room temperature, and the reaction time is 30-80 min, preferably 50 min.

8. A composite nanofiltration membrane with a tannic acid structure obtained by the preparation method according to any one of claims 1 to 6.

9. Use of the composite nanofiltration membrane with tannic acid structure as claimed in claim 8.

10. The use according to claim 9, characterized in that: Applied to the removal of dyes and the separation of salts, preferably, the dye is an anionic dye; preferably, the anionic dye is one of Congo red, reaction red 120, or orange yellow or a mixture thereof; and the salt is NaCl or Na2SO4.

Citation Information

Cited By

  • Preparation method of uniform and compact alcohol-permselective composite membrane

    CN119425411A

  • Synthesis of polyphenol monomer and preparation method of loose nanofiltration membrane

    CN119823003A